EFL Students’ Perceptions of Digital Extensive Reading Program in Junior High School Level - Yesri Imawati Saefatu; Ali Mustofa; Pratiwi Retnaningdyah (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2023)
The digital extensive reading have important thing in studying English for junior high school. In this study investigated the students’ perceptions of digital extensive reading. The participants are the students of seventh grade students of SMP Negeri 2 Soe which consists of 29 students. This study applied qualitative research method. The researcher collected the data through observing and interview. The media used Let’s Read application as digital media. The results of students’ perceptions of digital extensive reading are students feel happy, fun, exciting and good. The strength of digital extensive reading, so many variety stories, have pictures, the text are simple sentences, and can translate directly. The weaknesses of digital extensive reading are eye damage and need internet connection. The impact that students get after using digital extensive reading are they rich new vocabularies, improve reading fluency, improve reading skill, read a lot of stories, and increase knowledge.